UPAYA PENINGKATAN HASIL BELAJAR IPA MELALUI METODE JIGSAW DI KELAS IV SD NEGERI NO. 91/VI RANTAU PANJANG VI KECAMATAN TABIR KABUPATEN MERANGIN - Jasmarizal (Mat-Edukasia, 2021)
This study aims to determine the increase in science learning outcomes by applying the Jigsaw method to fourth grade students of SD Negeri No. 91/VI Rantau Panjang VI, Merangin District, Semester 2 of the 2017/2018 Academic Year. This type of classroom action research (CAR) consists of 3 cycles. The research subjects were all fourth grade students, totaling 16 students. The instruments used were observation sheets and formative tests at the end of the cycle. The criteria for success in this study are 80% of all fourth grade students have reached or exceeded the Minimum Completeness Criteria (KKM) which is 70 with the formula for average scores and percentages. The results showed that the application of the Jigsaw method could improve learning in cycle I, cycle II, and cycle III, student learning outcomes increased, namely the results of pre-cycle formative tests, the average grade 50 of 16 students, with details of students who completed only 2 students 13%) and 14 students (87%). Cycle I average grade 70 out of 16 students, 12 students (75%) completed and 2 (25%). Cycle II the average grades increased to 80 out of 16 students, while those who completed 14 students (88%), who had not completed 2 students (12%). Cycle III the average value of the class increased to 84 out of 16 students, as for those who completed 16 students (100%), those who had not completed 0 students (0%)